Systems and methods for automated query answer generation - Tiwary, Saurabh Kumar; Rosenberg, Mir; Gao, Jianfeng; Song, Xia; Majumder, Rangan; Deng, Li (Google Patents, 2018)
Systems and methods for automated generation of new content responses to answer user queries are provided. The systems and methods for automated generation of new content responses answer user queries utilizing deep learning and a reasoning algorithm. The generated response is composed of new content and is not merely cut or copied information from one or more search results. Accordingly, the systems and methods for automated generation of new content responses provide tailored query specific answers that can be long and detailed including several sentences of information or that can be short and concise, such as “yes” or “no.” The ability of the systems and methods described herein to create or generate new content in response to a user query improves the usability, improves the performance, and/or improves user interactions of/with a search query system.